EFFECT OF SPINDLE ROTATION IN TURNING HIGH CARBON STEEL USING HSS LATHE BLADES ON SURFACE ROUGHNESS AND INTEGRITY OF LATHE BLADES - Muhamad Jafri (Universitas Muhammadiyah Semarang, 2023)
This experiment aims to determine the effect of spindle rotation on medium carbon steel turning using an HSS knife, the roughness of the object and the integrity of the blade. In the field of machining, the surface quality of an object can be influenced by several factors such as cutting speed, cutting speed, cutting angle, depth of cut and the material used in the turning process. A good lathe knife must have certain properties, so that later it can produce products with good quality (right size) and economical (short time required). The spindle lathe speed set by the workshop technician for fine-working medium carbon steel is 200 rpm. However, if analyzed using the existing theory, the spindle rotation for medium carbon steel is obtained and for the same HSS lathe, the spindle rotation is 1600 rpm. This can result in surface roughness and defects in the lathe blade, which can vary from small to large. The results showed that the inappropriate selection of spindle rotation when turning medium carbon steel using HSS resulted in defects in the lathe. Defects in the blade affect the surface roughness of the object.